PENGELOLAAN MEDIA SOSIAL TWITTER OLEH KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN DALAM SOSIALISASI PERPRES PENGUATAN PENDIDIKAN KARAKTER - Miranda, Ardanari (Universitas Mercu Buana, 2019)
Management of social media, especially the Twitter account of the Ministry of Education and Culture @Kemdikbud_RI. This research is to find out about the management of Kemdikbud_RI's Twitter account in the socialization of the Perpres Strengthening Character Education. The theory used in this study about the management of social media, which includes the processes of planning, activation and supervision, optimization, social media activities, social media strategies, implementation, and to the process of monitoring and evaluation. Case study research method that aims to describe and describe systematically a fact carefully. Data collection techniques using primary and secondary data. Primary data were obtained by in-depth interviews with the Head of the Communication and Public Service Bureau, the Head of Information Services Subdivision and the admin of the Ministry of Education and Culture's social media. Secondary data obtained from pages, books and other documents. The results showed that, the Communication and Public Service Bureau had Standard Operating Procedures in managing the social media accounts of the Ministry of Education and Culture and had grouped the community based on the followers of each social media account (Twitter, Facebook, Instagram, Website, YouTube) owned by the Ministry of Education and Culture, so it is clear what content will be uploaded, so that followers / followers from each account will find it easier to understand the policies that have been conveyed through the Ministry of Education and Culture's social media.